The role of the people of Yemen in the battle of Yarmouk and beyond - العلو, فراس; محسن يونس , (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The Yemeni Arabs occupied aprominent role in the history of the Arabs and islam since the beginning of the Islamic call and throughout the successive historical eras starting from the era of the Messenger, may Gods prayers and peace be upon him, the passage of the era of the Rightly Guided caliphs and the era of the Umayyad, Abbasid and Middle Ages until our modern and contemporary history, and perhaps their distinguished role in the Arab Islamic conquests it was an important turning point in our Arab – Islamic history, which was evident in their fighting the decisive battles on the front of Iraq and the levant in Qadisiyah and Yarmouk. We saw that it is very important to shed light on the role they played in the Battle. They recruited fighters and experienced leaders, which enabled them to achieve victory over the Romans and liberate the levant from the company of foreign occupiers. Then they settled in the liberated areas, so it was necessary for us working in the historical research is to highlight this role through what the historical sources mentioned with all honesty and sincerity as much as we can to achieve that as away.